Behavior of Human Antibiotics in Wastewater Treatment Plants - YASOJIMA, Makoto; KOBAYASHI, Yoshikazu; TANAKA, Hiroaki; KOMORI, Koya; SUZUKI, Yutaka; NAKADA, Norihide (ENVIRONMENTAL ENGINEERING RESEARCH, 2005)
Antibiotics resident in sewage and in the water environment have become an emerging public concern in many developed countries. Also in Japan, studies about their concentrations in the environment and in the discharge from sewage treatment plants have begun to be reported. The objectives of this research were to clarify the behavior in sewage treatment plants about selected human antibiotics, namely levofloxacin (LVFX), clarithromycin (CAM) and azithromycin (AZM). In samples of filtered influents and secondary effluents, average concentrations of LVFX, CAM and AZM were 552, 301ng/L, 647, 359ng/L and 260, 138ng/L, respectively. Removal efficiencies of LVFX, CAM and AZM in sewage treatment plants were 46%, 45% and 47%, respectively. These removal efficiencies and sludge retention time (SRT) in their reactors had some correlation. When the pH dependability of octanol-water partition coefficients (Kow) of LVFX, CAM and AZM was examined in this study, clear pH dependability was observed in the range from pH 3 to 9. As a result of batch test of sorption to activated sludge, sorption was suggested to be major removal mechanism for LVFX and AZM. On the other hand, biodegradation was suggested to be major removal mechanism for CAM. Further, behavior of these antibiotics including suspended solid and activated sludge was clarified in a pilot plant. As a result of this survey, one to ten times high concentrations of LVFX, CAM and AZM in activated sludge was detected than water phase, which demonstrated that these antibiotics tend to be sorbed to activated sludge. However, Log Kow alone was not able to explain this adsorption phenomenon. In contrast, Log Kd had a possibility that it could be explained.